2020
DOI: 10.1007/s00330-020-06690-3
|View full text |Cite
|
Sign up to set email alerts
|

Post-contrast acute kidney injury in a hospitalized population: short-, mid-, and long-term outcome and risk factors for adverse events

Abstract: Objectives To investigate the prognosis including major adverse kidney events within 30 days (MAKE30) and 90-day and 1-year adverse outcome in hospitalized patients with post-contrast acute kidney injury (PC-AKI) to identify high-risk factors. Methods This retrospective observational study included 288 PC-AKI patients selected from 277,898 patients admitted to hospitals from January 2015 to December 2015. PC-AKI was defined according to the 2018 guideline of European Society of Urogenital Radiology. Multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 59 publications
(66 reference statements)
0
15
0
2
Order By: Relevance
“…As studies have consistently shown that an episode of AKI was associated with increased risks for requirement of renal replacement therapy, subsequent CKD and mortality ( Bucaloiu et al, 2012 ; Cheng et al, 2020 ; Hoste et al, 2018 ; Linder et al, 2014 ), whether the association between AKD and adverse outcomes in 30 days and one year was resulted from the impact of AKI stage was unclear. Therefore, we stratified the patients by both AKI stage and AKD stage.…”
Section: Discussionmentioning
confidence: 99%
“…As studies have consistently shown that an episode of AKI was associated with increased risks for requirement of renal replacement therapy, subsequent CKD and mortality ( Bucaloiu et al, 2012 ; Cheng et al, 2020 ; Hoste et al, 2018 ; Linder et al, 2014 ), whether the association between AKD and adverse outcomes in 30 days and one year was resulted from the impact of AKI stage was unclear. Therefore, we stratified the patients by both AKI stage and AKD stage.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al reported that oliguria was an independent risk factor of 90-day or 1-year adverse prognosis (P<0.05) in hospitalized patients with post-contrast acute kidney injury. 26 Similarly, a nationwide survey of patients with AKI revealed that oliguria occurrence at the time of AKI diagnosis was an independently significant prognostic indicator of in-hospital mortality. 27 Transient oliguria may have a relatively benign nature; however, it is still a symptom of which clinicians must remain aware.…”
Section: Discussionmentioning
confidence: 99%
“…En tal sentido se identificó la anemia como FR independiente de nefropatía por contraste (Mehran, et al, 2019). Otros autores describen una incidencia entre 6,2 y 26,2% (Cheng, et al, 2020).…”
Section: Discussionunclassified
“…Esta necesaria exposición implica el riesgo de reacciones adversas, de las cuales, una de las más temidas es el daño renal agudo inducido por MC, o nefropatía inducida por medios de contraste (NIC). Esta complicación, sin duda, puede empeorar el pronóstico vital y aumenta la mortalidad de los pacientes afectos (Cheng, et al, 2020).…”
Section: Introductionunclassified